2020
DOI: 10.1186/s12864-020-6755-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of human thymic CD4+ and CD8+ T cells compared to primary peripheral T cells

Abstract: Background: The thymus is a highly specialized organ of the immune system where T cell precursors develop and differentiate into self-tolerant CD4+ or CD8+ T cells. No studies to date have investigated how the human transcriptome profiles differ, between T cells still residing in the thymus and T cells in the periphery. Results: We have performed high-throughput RNA sequencing to characterize the transcriptomes of primary single positive (SP) CD4+ and CD8+ T cells from infant thymic tissue, as well as primary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…6d ). 24 27 The results showed that various clinical features affect the patient’s T cell immunity, but cannot change its tendency to become robust during recovery from COVID-19.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…6d ). 24 27 The results showed that various clinical features affect the patient’s T cell immunity, but cannot change its tendency to become robust during recovery from COVID-19.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Myeloid cells were defined by canonical markers Cd11b and Cd74 ( 28 ), but other noncanonical markers were also observed, including Myo1f ( 29 ) and Tgfb ( 30 ). Lymphocytes showed a similar mix of broad and specific expression patterns of cell type markers, with expression of pan-lymphocyte marker Il18r1 , T lymphocyte marker Prkcq , and cytotoxic T cell marker Cd8b ( 31 33 ). Last, we detected a cluster of MSCs/stromal cells that expressed both broad mesenchymal cell markers Rbms3 and Tshz2 and stem/stromal cell markers Prkg1 and Gpc6 (fig.…”
Section: Resultsmentioning
confidence: 97%
“…Still, most biomarkers in plasma and T-cell did not improve and were far from normalization compared to HIV-monoinfected patients [ 40 ]. Moreover, we explored the specific signatures of lymphocytes T CD4 + and CD8 + , based on previous transcriptome profiling on these cells [ 94 , 95 ], but none of these genes were identified as differentially expressed after HCV eradication.…”
Section: Discussionmentioning
confidence: 99%